Report of the Committee Appointed by the Government of India to Advise them on the steps to be taken to Establish a Research Centre in the Indigenous Systems of Medicine and Other Cognate Matters - Ministry of Health (Ministry of Health, 1949)
The Indian Government-appointed Committee on Indigenous Systems of Medicine proposes the establishment of a dedicated research center to advance Ayurveda and Unani practices through modern scientific methodologies. Located in Jamnagar, the center would integrate a hospital for clinical studies and focus on literature, pharmacology, and psychological research within traditional frameworks. Recommendations emphasize curriculum integration in modern medical colleges, postgraduate opportunities, higher admission standards, and collaboration between indigenous and contemporary medical professionals. Financial planning, staffing strategies, and governance frameworks are outlined to ensure operational effectiveness. The initiative aims to standardize Ayurvedic and Unani education, enhance research capabilities, and position traditional Indian medicine within a globally relevant, scientifically validated healthcare framework, promoting long-term sustainability and integration with contemporary medical practices.
Ministry of Health
Keywords: Indigenous Medicine; Ayurveda; Unani; Research Centre; Medical Education; Curriculum Integration; Clinical Research; Standardization; Government Policy; Traditional Medicine